2013
DOI: 10.1111/acfi.12044
|View full text |Cite
|
Sign up to set email alerts
|

How do auditors perceive CEO's risk-taking incentives?

Abstract: Prior literature documents that executive compensation influences managerial risk preferences through executives' portfolio sensitivities to changes in stock prices (delta) and stock-return volatility (vega). Large deltas discourage managerial risk-taking, while large vegas encourage risk-taking. Theory suggests that auditors charge higher audit fees when standard audit procedures do not allow auditors to reduce audit risk including the risk arising from higher business risk. We posit and find evidence of a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
3
23
1
2
Order By: Relevance
“…Corporate governance is included as a control variable for cost of debt given that it potentially improves compliance with reporting standards and generates financial statements that provide a more accurate reflection of a company's performance (Davidson et al ., ; Kent et al ., ; Fargher et al ., ). To control for the association between corporate governance quality and the cost of debt, we use a scoring system related to Corporate Governance Principles and Recommendations (Australian Security Exchange Corporate Governance Council, ).…”
Section: Methodsmentioning
confidence: 97%
“…Corporate governance is included as a control variable for cost of debt given that it potentially improves compliance with reporting standards and generates financial statements that provide a more accurate reflection of a company's performance (Davidson et al ., ; Kent et al ., ; Fargher et al ., ). To control for the association between corporate governance quality and the cost of debt, we use a scoring system related to Corporate Governance Principles and Recommendations (Australian Security Exchange Corporate Governance Council, ).…”
Section: Methodsmentioning
confidence: 97%
“…We include LEV, measured by the total debt divided by total assets (Subramaniam et al, 2009;Oliveira et al, 2011;Kent and Zunker, 2013;Tao and Hutchinson, 2013). We include BIG4 to control for audit quality, as Big 4 audit firms are associated with higher audit quality (Fargher et al, 2014;Miglani et al, 2015). Following Matsumoto (2002), we include LOSS because loss firms are less likely to be involved in fraudulent financial reporting.…”
Section: Empirical Modelsmentioning
confidence: 99%
“…We also include F_AGE, measured by the number of years a firm has been listed (Huang et al, 2012;Abdel-khalik, 2014). We include BIG4 to control for audit quality, as Big 4 audit firms are associated with higher audit quality (Fargher et al, 2014;Miglani et al, 2015).…”
Section: Empirical Modelsmentioning
confidence: 99%
“…Using the U.S. Audit Analytics database for the period 2000-2010, Fargher et al (2014) [17] found evidence that executive equity incentives as proxies for managerial risk-taking incentives have a significant impact on audit fees, as well as the issuance of going-concern audit opinions. With the U.S.…”
Section: Relationship Between Executive Stock Options and Audit Feesmentioning
confidence: 99%